Phenotypic stability and adaptability of wheat genotypes under organic and conventional farming systems over five years using AMMI and GGE biplot analysis - Al-Ghumaiz, Nasser S.; Motawei, Mohamad I.; Aggag, Ahmed M.; Al-Otayk, Soleman M.; Alzamil, Abdulmajeed A. (Frontiers in Plant Science, 2025)
Organic agriculture is recognized for its sustainability, although it typically yields less than conventional systems. This study evaluated seven elite wheat genotypes (Triticum aestivum L.) over five years in a randomized complete block design with three replications, under both organic and conventional fertilization conditions. Integrated analyses using the AMMI model and GGE biplot revealed the significant effects of genotype, environment, and their interactions. The AMMI analysis showed that genotype IC8 achieved the highest mean yield (1.868 t ha-1) and the lowest AMMI stability value (ASV=0.474). This low ASV suggests high stability, indicating broad adaptability, especially under organic conditions. In contrast, Sids_12 (mean = 1.492 t ha-1; ASV=2.017) and LOCAL (mean = 1.304 t ha-1) exhibited great instability and specific adaptation. GGE biplot analysis explained 75.46% of the total variation (PC1 = 57.09%, PC2 = 18.37%), further confirming IC8’s stable performance across both systems while identifying P5 and IC17 as particularly responsive under conventional fertilization. These findings provide a basis for selecting wheat genotypes that balance high yield and stability, informing breeding strategies for sustainable crop production in both organic and conventional systems.